Quickness and agility: comparison between agonistic rhythmic and artistic gymnastics in evolutive age - Scotton, C.; Viviano, G.; Ferraris, L.; Guidotto, F.; Lupo, C. (Medicina dello Sport, 2017)
BACKGROUND: This study analyzed the differences between artistic and rhythmic gymnastics on quickness (30-s-hand and foot tapping tests) and agility (5 x 5 m shuttle run test with inversion of direction) capabilities, which were tested at the beginning (pre) and end (post) of training session. METHODS: The above mentioned tests were performed seven times by 24 agonistic gymnastics (artistic gymnastics: N.=12, age=14.5±1.5 years; rhythmic gymnastics: N.=12, age=14.5±1.5 years) during seven corresponding training sessions. RESULTS: Results showed a difference for the feet tapping test (pre, P=0.002; post, P=0.013), where the artistic gymnastics (pre=99±7, post=101±7) reported a better performance with respect to the rhythmic ones (pre=95±5, post=96±6). On the other hand, an opposite picture with an approach to the significance (P=0.059) emerged for the post hand tapping test (artistic gymnastics=126±11, rhythmic=128±13). No difference was reported for the agility test (pre and post) as well as for the pre-post comparisons applied to each gymnastic subgroups and test. CONCLUSIONS: These findings suggested a potential relationship between foot tapping (and lower limbs coordination) and artistic gymnastics, in which the proprioception of feet is highly trained because of the "beam" contact and the related requests of balance and change of directions. Different conclusions can be provided for the other trials, where rare divergences tend to define an equal development of the hand tapping and agility capabilities. Finally, the absence of effects for the pre-post comparison highlights the presence of two opposite factors due to training load: the fatigue, which tends to minimize performance, and the neuromuscular activation, which tends to improve it.